Mewujudkan Keadilan dan Kesetaraan Melalui Perlindungan Hak Asasi Manusia : Edukasi Stop Bullying di SMPN 11 Kota Serang - Nadofah Nadofah; Devi Ayu Kurniawati; Ulinnuha (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Bullying is a common practice, especially in schools, and requires attention from various parties. One approach is to provide education on bullying and prevent human rights violations. This community service activity is a contribution from academics to promote the importance of understanding human rights protection and addressing bullying behavior in schools. The purpose of this outreach is to increase knowledge, build legal awareness among students and educators in the school environment, strengthen humanitarian values, and encourage the creation of safe, harmonious, and inclusive schools. This study used the Participatory Action Research (PAR) method. The results of the outreach show an increase in student knowledge regarding bullying. Students are able to understand children's rights, the impacts, and how to deal with bullying that occurs to themselves or in their surroundings.